Bromopride, metoclopramide, or ondansetron for the treatment of vomiting in the pediatric emergency department: a randomized controlled trial - Matias Epifanio; Janete de L. Portela; Jefferson P. Piva; Cristina H. Targa Ferreira; Edgar E. Sarria; Rita Mattiello
Abstract Objective: To compare the effectiveness of a single intramuscular dose of bromopride, metoclopramide, or ondansetron for treating vomiting. Methods: Randomized controlled trial including children 1-12 years of age presenting with acute vomiting at the pediatric emergency department. Outcomes: Number of children that stopped vomiting at one, six, and 24 h following treatment; episodes of diarrhea; acceptance of oral liquids; intravenous rehydration; return to hospital and side effects. Results: There were 175 children who completed the study. Within the first hour after treatment, all drugs were equally effective, with ondansetron preventing vomiting in 100%, bromopride in 96.6%, and metoclopramide in 94.8% of children (p = 0.288). Within six hours, ondansetron was successful in preventing vomiting in 98.3% of children, compared to bromopride and metoclopramide, which were successful in 91.5% and 84.4% of patients, respectively (p = 0.023). Within 24 h, ondansetron was superior to both other agents, as it remained efficacious in reducing vomiting in 96.6% of children, as opposed to 67.8% and 67.2% with bromopride and metoclopramide, respectively (p = 0.001). The ondansetron group showed better acceptance of oral liquids (p = 0.05) when compared to the bromopride and metoclopramide. The ondansetron group did not show any side effects in 75.9% of cases, compared to 54.2% and 53.5% in the bromopride and metoclopramide groups, respectively. Somnolence was the most common side effect. Conclusions: A single dose of ondansetron is superior to bromopride and metoclopramide in preventing vomiting six hours and 24 h following treatment. Oral fluid intake after receiving medication was statistically better with Ondansetronwhile also having less side effects compared to the other two agents.